Freedom from poverty: NGOs and human rights praxis - Chong, Daniel P. L. (Pennsylvania studies in human rights, 2010)
NGOs and freedom from poverty -- A social theory of human rights -- Human rights organizations -- Social justice organizations -- Humanitarian organizations -- Using a social theory to interpret NGO efforts